IN NEED OF CRITERIA TO EVALUATE ELT TEXT BOOKS - YE. Budiyana (Celt: A Journal of Culture, English Language Teaching & Literature, 2002)
With reference to the introduction of English teaching at the Primary Schools in Indonesia, textbooks are very important things to deal with due to the fact that these are considered as "the visible heart of the ELT programme" for both students and teachers (Sheldon 1988:237). To meet the needs of the textbooks, schools buy textbooks commercially published by local andforeign publishers, whose writers are native speakers. They normally live in their own culture, and therefore find it hard to compose data beyond their own culturcl boundaries. Its a result, the definition and application of systematic criteria for assessing those published by local as well as foreign publishers are vital. By identifying the potential strengths and weaknesses of textbooks in general with the suggested criteria, the teacher will have a comparative basis for making decisions and he! she is unlikely to make a bad choice of textbooks.